Ferric Gluconate Is Highly Efficacious in Anemic Hemodialysis Patients with High Serum Ferritin and Low Transferrin Saturation: Results of the Dialysis Patients’ Response to IV Iron with Elevated Ferritin (DRIVE) Study - Coyne, Daniel W.; Kapoian, Toros; Suki, Wadi; Singh, Ajay K.; Moran, John E.; Dahl, Naomi V.; Rizkala, Adel R. (Journal of the American Society of Nephrology, 2007)
Few data exist to guide treatment of anemic hemodialysis patients with high ferritin and low transferrin saturation (TSAT). The Dialysis Patients' Response to IV Iron with Elevated Ferritin (DRIVE) trial was designed to evaluate the efficacy of intravenous ferric gluconate in such patients. Inclusion criteria were hemoglobin <or=11 g/dl, ferritin 500 to 1200 ng/ml, TSAT <or=25%, and epoetin dosage >or=225 IU/kg per wk or >or=22,500 IU/wk. Patients with known infections or recent significant blood loss were excluded. Participants (n=134) were randomly assigned to no iron (control) or to ferric gluconate 125 mg intravenously with eight consecutive hemodialysis sessions (intravenous iron). At randomization, epoetin was increased 25% in both groups; further dosage changes were prohibited. At 6 wk, hemoglobin increased significantly more (P=0.028) in the intravenous iron group (1.6 +/- 1.3 g/dl) than in the control group (1.1 +/- 1.4 g/dl). Hemoglobin response occurred faster (P=0.035) and more patients responded after intravenous iron than in the control group (P=0.041). Ferritin <or=800 or >800 ng/ml had no relationship to the magnitude or likelihood of responsiveness to intravenous iron relative to the control group. Similarly, the superiority of intravenous iron compared with no iron was similar whether baseline TSAT was above or below the study median of 19%. Ferritin decreased in control subjects (-174 +/- 225 ng/ml) and increased after intravenous iron (173 +/- 272 ng/ml; P<0.001). Intravenous iron resulted in a greater increase in TSAT than in control subjects (7.5 +/- 7.4 versus 1.8 +/- 5.2%; P<0.001). Reticulocyte hemoglobin content fell only in control subjects, suggesting worsening iron deficiency. Administration of ferric gluconate (125 mg for eight treatments) is superior to no iron therapy in anemic dialysis patients receiving adequate epoetin dosages and have a ferritin 500 to 1200 ng/ml and TSAT <or=25%.